BlpU is a broad-spectrum bacteriocin in Streptococcus thermophilus - Renye, John A.; Somkuti, George A.; Qi, Phoebe X.; Steinberg, Dennis H.; McAnulty, Michael J.; Miller, Amanda L.; Guron, Giselle K. P.; Oest, Adam M. (Frontiers in Microbiology, 2024)
Streptococcus thermophilus strain B59671 naturally produces thermophilin 110, a broadspectrum bacteriocin encoded within the bacteriocin-like peptide (blp) gene cluster, and thermophilin 13 from a separate chromosomal locus. Analysis of the blp gene cluster revealed two genes, blpU and blpK, as potentially encoding bacteriocins. Deletion of blpK from the B59671 chromosome did not result in a loss of antimicrobial activity against either S. thermophilus ST113 or Pediococcus acidilactici F. A deletion mutant of blpU could not be generated in B59671, but the mature BlpU peptide obtained through overexpression in E. coli BL21 or chemical synthesis inhibited the growth of S. thermophilus strains, Streptococcus mutans UA159, P. acidilactici F, and Listeria innocua GV9 L-S, evidencing as a broad-spectrum bacteriocin that does not require modification for activity. This study also showed that the transcription of blpU was approximately 16-fold higher in B59671 than in an induced culture of S. thermophilus LMD-9, which produces a blp-encoded bacteriocin. The increased expression of BlpU in B59671 may explain the unique antimicrobial spectrum associated with this strain.Additionally, it was shown that a blpC deletion mutant of B59671, which prevents expression of BlpU and BlpK, inhibited the growth of other S. thermophilus strains and Bacillus cereus, suggesting that thermophilin 13 produced by B59671 possessed both intra-and interspecies antimicrobial activity. While this study confirmed that BlpU can function as an independent antimicrobial peptide, further studies are required to determine if BlpK can function independently as a broad-spectrum antimicrobial.